2005
DOI: 10.1007/s00404-005-0032-z
|View full text |Cite
|
Sign up to set email alerts
|

A study of abnormal cervical cytology in pregnant women

Abstract: During the 4 year routine study of smears in 2,919 pregnant women, 33 cases of abnormals of the uterine cervix were detected (1.13%). The patients were followed with uterine cervical cytology and colposcopy and in case of need, sometimes punch biopsies were performed. The results of the cytologies, 33 cases with abnormalities were detected. There were 26 cases classified as class IIIa, 7 cases were class IIIb. All the cases underwent colposcopy. For the 17 cases that showed lesions by colposcopy, and punch bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
2
1
Order By: Relevance
“…Therefore, routine antenatal Pap smear is such an important examination. Abnormal cervical cytology is observed in about 5% of gravidas [17][18][19]. In our study the percentage was slightly lower than the average -2.3%.…”
Section: 2% Respectively)contrasting
confidence: 59%
“…Therefore, routine antenatal Pap smear is such an important examination. Abnormal cervical cytology is observed in about 5% of gravidas [17][18][19]. In our study the percentage was slightly lower than the average -2.3%.…”
Section: 2% Respectively)contrasting
confidence: 59%
“…among the infections of sexual transmission -overalls the human viral papilloma [7,8] and the cervical cancer justifies that the growing behavior of the first ones mainly at the end of the second and third decades of life it makes that cases of cancer appear in young ages.…”
Section: Introductionmentioning
confidence: 99%
“…The annual report of the Gynecologic Cancer Committee of the Japan Society of Obstetrics and Gynecology in 2005 [1] reported that 77.0% of stage 0 and 43.6% of stage Ia1 cervical cancers were treated by conization. Early-stage cervical cancer frequently occurs at a young age, and the frequency of abnormal cervical cytology in pregnant women has increased from 0.8 % [2] to 1.13% [3] over the past 10 years in Japan. We retrospectively examined results of long-term follow-up to evaluate the efficacy and safety of CO 2 laser conization for pregnant women with biopsy-proven cervical intraepithelial neoplasia 3/carcinoma in situ (CIN3/CIS) or microinvasive carcinoma (MIC) of the uterine cervix.…”
Section: Introductionmentioning
confidence: 99%